CREATIVE INDIVIDUALITY IN EARLY STORIES (Scientific journal of the Fergana State University, 2024)
In the article, although the story described in the stories of the special place of Anvar Obidjon's work does not differ in its essence and importance from genres of the epic type, such as novels and short stories, the scope of the image, the relative simplicity of the plot and composition, and the fact that the narration is mainly carried out by one person are highlighted in the article. Also, "The story, as a rule, covers one (sometimes several interrelated events that took place over a short period of time) from the life of the hero. The short duration of the depicted events requires that the story is small in size, the plot is simple, and the number of participants is small. It is stated that not every event is a story chapter.